COINAGE: A PROCESS OF COMPOUNDING IN ÀGÀTÚ - Umaru, Yakubu Jacob (EBSU Journal of Social Sciences and Humanities, 2024)
The paper considers the morphology of Àgàtú, taking into consideration coinage as a process of compounding in Àgàtú. This study, therefore, describes Àgàtúcompounding from the view point of coinages and adopts a descriptive method to analyse coinages. The description is based on coinage as a morphological process of compounding in Àgàtú. The data were elicited using a list of novel concepts and interview with native speakers who are bilingual in both English and the language. The data collected were analyzed by describing the data provided by the native speakers. The study establishes that coined words are used as a means of extending the lexicon of the language through the creation of new lexical categories. Such ideas, concepts and institutions are derived through the device of reduplication process, where nominals are compounded to form new lexemes with the status of compound nouns in the language. One morphophonemic rules play out in the compounding and coinage process; elision and insertion; they are employed in the context where unacceptable vowel sequences occur within word boundaries. The research has made a modest contribution to the on-going research on novel concepts (coinages) of Àgàtú. It has also contributed to researches on indigenous Nigerian languages in general, Àgàtú in particular.